Improved Biomedical Properties of Polydopamine-Coated Carbon Nanotubes - Sahin Demirci (MDPI AG, 2021)
Carbon nanotubes (CNTs) due to their outstanding mechanical, thermal, chemical, and optical properties were utilized as a base material and were coated with polydopamine (PDA) (PDA@CNT) via the simple self-polymerization of dopamine (DA). Then, PDA@CNT coatings of up to five layers were examined for potential biomedical applications. The success of multiple coating of CNTs with PDA was confirmed via increased weight loss values with the increased number of PDA coatings of CNTs at 500 °C by thermogravimetric analysis. The surface area of bare CNTs was measured as 263.9 m2/g and decreased to 197.0 m2/g after a 5th coating with PDA. Furthermore, the antioxidant activities of CNT and PDA@CNTs were determined via total flavonoid content (TFC), total phenol content (TPC), and Fe(III)-reducing antioxidant power (FRAP) tests, revealing the increased antioxidant ability of PDA@CNTs with the increasing numbers of PDA coatings. Moreover, a higher inhibition percentage of the activity of the alpha-glucosidase enzyme with 95.1 ± 2.9% inhibition at 6 mg/mL PDA-1st@CNTs concentration was found. The CNT and PDA@CNTs exhibited blood compatibility, less than a 2.5% hemolysis ratio, and more than 85% blood clotting indexes. The minimum inhibition concentration (MIC) of PDA-5th@CNTs against E. coli and S. aureus bacteria was determined as 10 mg/mL.